Transport Costs and Prices in Lao PDR : Unlocking the Potential of an Idle Fleet - World Bank Group (World Bank, Washington, DC, 2018)
The cost of transport in Lao PDR is said to be higher than in neighboring countries, affectingthe competitiveness of producers and shippers alike. However, the picture appears to be morenuanced. Since there has not been much hard evidence to support this claim, this paper fills thegap by empirically investigating transport costs and prices for domestic routes in Lao PDR andidentifies the key drivers behind transport costs. The transport sector in Lao PDR can be describedas thin, consisting of a dozen large players (defined as having a fleet size of more than 50 trucks) and many small firms (companies with less than 5 trucks or owner-operators). Many of the micro firms work in the informal sector. Productivity levels in the Lao transport sector are generally very low. Across the study sample, the average annual distance driven per truck is only 55,000 km which is very low, though comparable to other landlocked, developing countries. Transport costs are on average LAK 489 per ton-km (equivalent to USD 0.06 per ton-km). A large majority of transport companies operate within a band of LAK 230 (USD 0.028) and LAK 575 (USD 0.07), of which variable costs make up 62 percent. Smaller firms tend to be less efficient than larger ones in spite of their much smaller overhead costs. The 25 percent cost advantage per ton-km of informal firms is offset by the economies of scale of larger firms that operate newer and larger trucks.